Association of Sporadic Moderate-Vigorous Physical Activity with Cardiovascular Disease Risk Factors - A Systematic Review - VP Putri (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Physical activity is an important factor controlling chronic diseases such as .....